(untitled) (Journal of Partial Differential Equations, 2015)
" In current paper, the coupled KdV (CKdV) system and Bosonized Supersymmetric Sawada-Kotera (BSSK) system are considered. Some linearly independent conservation laws for the two systems are derived via the first homotopy approach and symbolic computation."